A frequency‐reconfigurable triple‐band antenna with lumped components for wireless applications. Issue 6 (June 2015) - Zhai, Huiqing; Liu, Lu; Zhan, Chuanhan; Liang, Changhong
ABSTRACT: In this research, a new frequency‐reconfigurable triple‐band antenna for wireless applications achieved using lumped inductor is proposed. The each three working bands can be separately and continuously reconfigured by changing the values of the lumped inductors with the radiation patterns nearly unchanged. Besides, the working state can also be modulated to make the antenna operate at single‐band/dual‐band by selecting certain values of the lumped inductors. By introducing a via hole connecting the top layer patch with the bottom layer patch, a miniaturized size of 29 × 15 × 1.6 mm 3 can be achieved. The designed antenna has wide tunable band and can effectively covering 2.4/5.2/5.8 GHz Wireless Local Area Network and 3.5/5.5 GHz Worldwide Interoperability for Microwave Access bands. Besides, the designed antenna can also be applied for GSM850, GSM900, DCS1800, PCS1900, GPS, and 3G bands. The measured results have good agreement with the simulated results. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1374–1379, 2015